2019
DOI: 10.1590/s0102-865020190110000004
|View full text |Cite
|
Sign up to set email alerts
|

Biochanin A attenuates myocardial ischemia/reperfusion injury through the TLR4/NF-κB/NLRP3 signaling pathway

Abstract: Purpose:Myocardial ischemia/reperfusion (Ml/R) injury is a leading cause of damage in cardiac tissues, with high rates of mortality and disability. Biochanin A (BCA) is a main constituent of Trifolium pratense L. This study was intended to explore the effect of BCA on Ml/R injury and explore the potential mechanism.Methods: In vivo MI/R injury was established by transient coronary ligation in Sprague-Dawley rats. Triphenyltetrazolium chloride staining (TTC) was used to measure myocardial infarct size. ELISA as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…However, only the expressions of BAFF, BAFF-R, IL-1b, and IL-8 were changed rather than C1GALT1 and Cosmc when knocking down the expression of TLR4 ( Figure 5 and Supplemental Figure 2). Previous studies had demonstrated that the expressions of IL-1b and IL-8 could regulate the concentration of IgA and TLR4/NF-kB axis could modulate the expression of IL-1b and IL-8 (42)(43)(44). In present study, we also found that overexpression of TLR4 could active the NF-kB p65 signaling pathway.…”
Section: Discussionsupporting
confidence: 77%
“…However, only the expressions of BAFF, BAFF-R, IL-1b, and IL-8 were changed rather than C1GALT1 and Cosmc when knocking down the expression of TLR4 ( Figure 5 and Supplemental Figure 2). Previous studies had demonstrated that the expressions of IL-1b and IL-8 could regulate the concentration of IgA and TLR4/NF-kB axis could modulate the expression of IL-1b and IL-8 (42)(43)(44). In present study, we also found that overexpression of TLR4 could active the NF-kB p65 signaling pathway.…”
Section: Discussionsupporting
confidence: 77%
“…Studies have proved that many flavonoids possessed unique antioxidants and protection against myocardial I/R injury [45][46][47]. Kaempferol, a naturally occurring flavonoid, also has a very good antioxidant, anti-inflammatory, and cardioprotective properties in myocardial I/R injury [11,12].…”
Section: Plos Onementioning
confidence: 99%
“…To determine the mechanism of drug action, the classic in ammation-related TLR4/NF-κB signaling pathway was assayed. Bai Y. et al determined that biochanin A attenuates myocardial ischemia-reperfusion injury via the TLR4/NF-kappaB/NLRP3 signaling pathway [14]. HuaSheng D. et al determined that the HMGB1-TLR4 axis participates in myocardial ischemia-reperfusion injury by regulating myocardial cell apoptosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…Biochanin A can reduce the levels of IL-1β, IL-18, IL-6, and TNF-α in the serum, inhibit the expression of related proteins TLR4, MyD88, NLRP3, ASC, and caspase-1, and inhibit the phosphorylation of IkB-α and NF-κB to suppress in ammation through the TLR4/NF-κB signaling pathway and thus protect the myocardium [14]. Luteolin protects cardiomyocytes from ischemia-reperfusion injury via the TLR4/NF-κB/NLRP3 pathway [15].…”
Section: Tlr4/nf-κb Signaling Pathwaymentioning
confidence: 99%